2014
DOI: 10.1186/1479-5876-12-75
|View full text |Cite
|
Sign up to set email alerts
|

Existence of a potential neurogenic system in the adult human brain

Abstract: BackgroundPrevailingly, adult mammalian neurogenesis is thought to occur in discrete, separate locations known as neurogenic niches that are best characterized in the subgranular zone (SGZ) of the dentate gyrus and in the subventricular zone (SVZ). The existence of adult human neurogenic niches is controversial.MethodsThe existence of neurogenic niches was investigated with neurogenesis marker immunostaining in histologically normal human brains obtained from autopsies. Twenty-eight adult temporal lobes, speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
89
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(97 citation statements)
references
References 87 publications
8
89
0
Order By: Relevance
“…Our study suggests that this correlation may be significant, because we have shown that the human brain expresses neurogenesis markers in a continuous area between the hippocampus and hypothalamus 26. This area is larger than previously thought and involves the circumventricular organs, where the BBB is absent.…”
Section: Rationale and Background Informationsupporting
confidence: 54%
See 1 more Smart Citation
“…Our study suggests that this correlation may be significant, because we have shown that the human brain expresses neurogenesis markers in a continuous area between the hippocampus and hypothalamus 26. This area is larger than previously thought and involves the circumventricular organs, where the BBB is absent.…”
Section: Rationale and Background Informationsupporting
confidence: 54%
“…This figure displays figures from histologically normal brains analyzed in our previous study,26 which showed the existence of a potential neurogenic system between the hypothalamus and the hippocampus. A and B are brain specimens showing the choroid plexus (1) and the fimbria (2), which are structures in the hypothalamus-hippocampus axis that express neurogenesis markers 26. The BBB is normally absent in the choroid plexus and in the neurovascular unit during brain injury, which may indicate a role of the neurovascular unit in injury-induced neurogenesis.…”
Section: Rationale and Background Informationmentioning
confidence: 94%
“…CC central canal, 3 V third ventricle diet-induced obesity model rodents (McNay et al 2012). Recently, the occurrence of NSCs and NPCs has been demonstrated in the ME and Arc of adult human brains (Sanin et al 2013;Nogueira et al 2014;Batailler et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in the human exocrine pancreas, nestin-positive endothelial cells are adjacent to regions in the ductal epithelium that harbor putative islet progenitor cells. 15 Furthermore, in our previous study, 12 One caveat of our study is that we only used one hepatocellular carcinoma case, yet the lack of information regarding a subject with such relevance and the results presented here warrant this report. For instance, although hepatocellular carcinoma is the fifth most frequent tumor type, its prognosis is highly heterogeneous.…”
Section: Discussionmentioning
confidence: 73%